A new color vep procedure discloses asymptomatic visual impairments in optic neuritis and glaucoma suspects - Accornero, N.; Gregori, B.; Galié, E.; De Feo, A.; Agnesi, R. (Acta neurologica Scandinavica, 2000)
Objective– To evaluate the reliability of visual evoked potentials obtained with a set of multiple chromatic and achromatic patterns (C‐VEPs) in differentiating asymptomatic perifoveal retinal impairment from central conduction impairment. Methods– We propose a set of colored pattern stimuli that allows relatively differential activation of the magnocellular and parvocellular pathways. The system runs on a standard Pentium PC with peripherals that present stimuli and collect, analyze and print data. P1 latencies of C‐VEPs obtained with achromatic (black/white) and chromatic (blue/black and red/black isocontrast) checkerboards were evaluated in normal subjects and patients with subclinical retinal impairment (glaucoma suspects) or mild neural conduction impairment (optic neuritis), none of whom had subjective visual defects. Results– The procedure evoked robust cortical signals and statistically distinguished the 3 groups of subjects. The achromatic and chromatic stimuli used distinguished controls from glaucoma suspects and patients with optic neuritis. Glaucoma suspects had greater impairment of C‐VEPs to blue/black checkerboards whereas patients with optic neuritis had greater impairment of responses to red/black stimuli. Conclusions– Our data suggest that chromatic patterns (color/black, red and blue), that may activate the parvocellular and magnocellular systems differentially but not selectively, can distinguish between mild perifoveal or foveal conduction impairment. They have the additional advantage of evoking large, stable responses across all the subjects.